The genetic polymorphisms of ZC3HC1 and SMARCA4 are associated with hypertension risk - Huijun Ma; Yongjun He; Mei Bai; Linhao Zhu; Xue He; Li Wang; Tianbo Jin (Molecular Genetics & Genomic Medicine, 2019)
Abstract Aim In this study, we aimed to evaluate the association between genetic variants of ZC3HC1 and SMARCA4 and hypertension risk in the Chinese Han population. Methods The Agena MassAssary platform was used to determine the genotypes of eight SNPs in ZC3HC1 and SMARCA4 from 350 hypertension patients and 483 healthy controls. Chi‐squared tests and genetic model were used to evaluate the associations. Odds ratios and 95% confidence intervals were calculated using unconditional logistic regression. The statistical power of this study was estimated through the Power and Sample Size Calculation online software. Result In the genetic model analysis, we identified that the SNP of rs1464890 in ZC3HC1 was associated with a 0.68‐fold decreased risk of hypertension in the codominant model and 0.65‐fold decreased risk in the dominant model. Rs4507692 in ZC3HC1 was associated with a 0.69‐fold decreased risk of hypertension in the codominant model and 0.66‐fold decreased risk in the dominant model. The genotype “G/A‐A/A” of rs11879293 and the genotype “G/T‐T/T” of rs1122608 in SMARCA4 were significantly associated with decreasing the hypertension risk. In addition, the “Ars2242487 Trs1464890 Trs4507692” ZC3HC1 haplotype was associated with a decreased risk of hypertension. Conclusion The present study suggested that ZC3HC1 and SMARCA4 polymorphism may conducive to play a protective role against the hypertension risk.